A device for centreless mechanical operation of cylindrical products made from polymeric composite material (PCM) - Самчук, Володимир Володимирович (Technology audit and production reserves, 2013)
During the past 10 years composite materials production has reached high volumes, among them composites made of polymeric materials take the significant place. As large number of the most popular products, made from PCM of different purpose has a cylindrical shape, there are high demands to the quality of their elements, their deviation from norms take place during processing. In the article there a device for centreless mechanical operation is considered. When using it the effectiveness of making products from PCM can be increased, especially in case of labour productivity and getting the more quality of treated surface, that can be reached by means of cutting force balancing and rotational moments, acting on the die in cutting zone and large quantity of cutting elements that have differently directed cutting edges.